Social media as a communication tool during emergencies and disasters in Ghana - Omar, Safianu (Department of Information Systems, 2025)
Problem Statement: The integration of social media into daily life has revolutionized information dissemination and communication practices, particularly in emergency and disaster management. While current research mainly focuses on one-way communication from Emergency and Disaster Management Organizations (EDMOs) to the public, there is a significant gap in understanding the potential for two-way communication and utilizing social media as a valuable data source. This research aims to address this gap by exploring how the EDMOs can leverage social media for effective communication during crises. The study covers aspects such as information dissemination strategies, public engagement, data analysis, social media resources, dynamic capabilities, and challenges and opportunities. By bridging this knowledge gap, the research aims to enhance communication outcomes, improve preparation for disaster events, and contribute to more informed and prepared emergency and disaster management strategies. Purpose of Study: The research focusses on examining the key role of social media as a communication tool within the context of emergency and disaster events. The study unravels the dynamics of social media communication within the realm of emergency and disaster management, emphasizing its transformative impact on information dissemination, retrieval, engaging with the public, and communication practices. Research Methodology: The study was guided by an interpretive research philosophy, emphasizing the social construction of knowledge. Recognizing gaps in the literature regarding the use of social media in emergency and disaster communication, the qualitative interpretive approach was chosen to explore experiences and perspectives. Qualitative methods, prioritizing participant insights, were considered essential for delving into the phenomena, uncovering implicit insights, and minimizing researcher bias. Adopting an exploratory case study method focusing on five EDMOs in Ghana, the study used purposive sampling involving twenty-seven participants. The focus was on how these EDMOs responded to the 2021 Accra floods and the Covid-19 pandemic. A hybrid inductive-deductive thematic analysis, aligned with the chosen theoretical frameworks –– the STREMII model, Resource-Based Theory (RBT), and the Dynamic Capability View (DCV) ––, was employed to gain a detailed understanding of social media utilization in emergency and disaster communication. The chosen frameworks provided a robust foundation for discussing the complexities of social media's role in disaster communication. Key Findings: The study yields practical insights, emphasizing the significance of strategic planning, resource allocation, and adaptability in leveraging social media effectively. The research findings encompass the recognition of social media as a crucial information source during emergencies and disasters, with the EDMOs utilizing social media platforms for real-time updates, crowdsourcing, and expert insights. The study underscores the pivotal role of EDMOs in disseminating essential information, particularly through proactive use of social media platforms, fostering community resilience and aiding coordination efforts. The results of the VI study also show that social media is a vital communication platform, allowing open dialogue between EDMOs and affected communities, addressing needs, and streamlining relief processes. Despite challenges, the study reveals that the EDMOs exhibited the capability to adapt and optimize resources dynamically, ensuring effective disaster response. The results culminated in the development of a new model which suggests a dynamic and responsive approach to disaster management through social media, aiming to enhance EDMOs' capacities and improve overall emergency and disaster outcomes. Contribution of the Study: The research advances knowledge, theory, and practice in disaster management communication. Firstly, the research yielded eight propositions, illuminating the diverse role of social media in disaster communication. Secondly, the study operationalised the STREMII model and expanded it by proposing a more adaptive model, considering the unpredictable nature of disasters and emergencies. This new model integrates aspects related to misinformation and supporting technologies during social media disruptions. Additionally, novel information gathering and dissemination strategies were introduced to enhance the STREMII model's applicability. The study also addressed gaps in the DCV and RBT theories, emphasizing the importance of intangible resources such as social media skills, collaborative networks, expert knowledge, protocols, guidelines, and adaptive learning culture. Continuous learning capability, connecting transformative capability with adaptability, was highlighted, bridging knowledge gaps in both theories. Furthermore, the concept of ordinary capabilities was introduced, stressing the significance of internal routine activities and processes in disaster management, often overlooked in the DCV and RBT theories. While dynamic capabilities are essential, the study argues that ordinary capabilities form the foundation for effective disaster response. The research also introduced collaborative capabilities exhibited by the EDMOs, emphasizing the establishment and management of relationships with external stakeholders. This enriched both the DCV and RBT theories, portraying collaboration as a dynamic capability within the DCV framework and a valuable resource within the RBT framework.